Penguatan Kesadaran Lingkungan melalui Penerapan Biopestisida Eco Enzyme Di Sekolah - Da Silva, Teodora; Fatma Puji Lestari; Atika Mutiarachim; Susan Ardelia; Bayu Ariyanto (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The community service program carried out at Stella Matutina Salatiga Junior High School aims to strengthen environmental awareness while supporting the implementation of sustainable education through the manufacture of biopesticides made from eco enzymes. This activity is based on students' low understanding of the impact of the use of synthetic chemical pesticides on health and the environment. Therefore, the program is designed for students to gain hands-on experience in processing organic waste into eco enzymes and using it as the main ingredient of environmentally friendly biopesticides. The implementation method includes socialization on the importance of protecting the environment, introduction to natural biopesticides, training in making biopesticides with simple techniques, and intensive assistance to teachers and students. The evaluation process was carried out through an interactive quiz using the Kahoot application to measure participants' understanding. In addition, the follow-up of the program includes the preparation of materials, creative workshops, the development of interactive modules, teacher training, classroom implementation, and exhibitions of student works. The results of the program showed that the training was effective, as evidenced by the application of biopesticides in school parks and the increase in student knowledge, namely from a pre-test score of 53% to 59% in the post-test. These findings confirm that the application of eco enzymes is not only beneficial in reducing the use of chemical pesticides, but also able to foster students' environmental awareness and practical skills. In the future, this program has the potential to be replicated in other schools as a project-based learning model that is applicable and sustainable.